Effect of sorghum flour treated with ozone and heat on the quality of gluten-free bread and cake - Marston, Kathryn G. (Kansas State University, 2009)
In order to improve the quality of products available for consumers who require a gluten-free diet, this study examined the effects of heat and ozone treatments on sorghum flour functionality in gluten-free bread and cake. In the ozone treatment experiment, commercially milled food-grade sorghum flour was subjected to ozone at the rate of 0.06 L/min for 15, 30, and 45 minutes. In the heat treatment experiment, commercially milled food-grade sorghum flour was subjected to dry-heat at two temperatures (95ºC and 125º) for 15, 30, and 45 minutes. Characterization of flour from each treatment included measurements of flour pH, color, and pasting properties. Evaluation of bread quality from each treatment included measurements of specific volume, color, crumb properties, and crumb firmness. Evaluation of cake quality from each treatment included measurements of specific gravity, volume, symmetry, uniformity, color, crumb structure, and crumb firmness. Bake testing using ozonated sorghum flour in a high-ratio white layer cake formulation showed that volume significantly increased (p<0.05) as ozonation time increased. Additionally, longer ozonation exposure times increased cells per slice area, lightness, and slice brightness values in gluten-free cakes while reducing crumb firmness. Despite improving lightness and slice brightness values, ozonation did not significantly increase (p>0.05) the specific volume of gluten-free batter based bread. In the heat treatment experiment, the optimum time and temperature relationship for improving sorghum flour was 125ºC for 30 minutes. This treatment level produced bread with the highest specific volume (3.08 mL/g) and the most cells per slice area (50.38 cells/cm2). This treatment level also produced cakes with the highest volume (72.17 cc) and most cells per slice area (79.18 cells/cm2). Additionally, cake and bread made from this heat treatment was deemed more acceptable in comparison to the control during consumer testing. The control sorghum flour in both studies produced breads and cakes with low volume, poor crumb properties, and dense textures. These results can assist in the product development process in advancing the quality of sorghum-based gluten-free foods for the consumers who require a gluten-free diet.
Keywords: Sorghum; Ozonation; Heat treatment; Gluten-free bread; Gluten-free cake; Agriculture, Food Science and Technology (0359)